Manfaat Homeopathy Bagi Pertahanan Tubuh Sapi Perah - Teguh Wibawan, I Wayan; Winny Kurniatanti Sanjaya, Agatha; -, Yusnani (Jurnal Veteriner; Vol 10 No 2 (2009), 2009)
The effectiveness of homeopathy combination in eliciting nonspecific cellular defense mechanism indairy cows is demonstrated in this study. Two groups of 2-7 years old, in 3-5 months term of pregnancydairy cows which suffering clinical mastitis were used id this study. At 3 weeks and 4 weeks prae partusanimals received their first homeopathy treatment, i.e. Group I: Coenzyme comp®, and Group II: a combinationof Mucosa comp® and Traumeel®, respectively. At one week and two weeks post partus all animals in thetwo groups received their second treatment, i.e. a combination of Lachesis comp® and Traumeel®.Subsequently, at 3 and 4 weeks post partus all animals in the two groups received their third treatment,i.e. a combination of Carduus comp® and Coenzyme comp®, respectively. All homeopathy solutions weregiven at 5 ml subcutaneously. Ten ml of blood samples for haptoglobin analysis were drawn from eachanimal and blood smears for White-Blood-Cell counting and differentiation and phagocytosis activity andcapacity observation were prepared from each animal at 3 and 4 weeks prae partus; and at one week, 3, 5,and 7 weeks post partus, respectively. Our results indicated that although there were non significantdifference in the phagocytosis activity and capacity between animals in Group I and Group II; animals inGroup II showed a marked increase in phagocytosis activity and capacity. Based on haptoglobin analysis,animals in Group II showed a steadily low haptoglobin level in the blood (0.08 mg/ml) up to 3 weeks postpartus and a tendency to further decline until the end of the observation. Based on the WBC counts anddifferentiation, animals in Group II also showed a better response compared to animals in Group I.In conclusion, the use of homeopathy combination is capable in eliciting nonspecific cellular defensemechanism; this phenomena were clearly shown in the combination of Mucosa comp® and Traumeel®. Theuse of this homeopathy combination should be considered at prae partus allowing the recognition of thehost defense mechanism.
Keywords: homeopathy, dairy cows, phagocytosis